Quantitative Bioanalytical Methods Validation and Implementation: Best Practices for Chromatographic and Ligand Binding Assays - Viswanathan, C. T.; Bansal, Surendra; Booth, Brian; DeStefano, Anthony J.; Rose, Mark J.; Sailstad, Jeffrey; Shah, Vinod P.; Skelly, Jerome P.; Swann, Patrick G.; Weiner, Russell (Pharmaceutical research, 2007)
The Third AAPS/FDA Bioanalytical Workshop, entitled "Quantitative Bioanalytical Methods Validation and Implementation: Best Practices for Chromatographic and Ligand Binding Assays" was held on May 1-3, 2006 in Arlington, VA. The format of this workshop consisted of presentations on bioanalytical topics, followed by discussion sessions where these topics could be debated, with the goal of reaching consensus, or identifying subjects where addition input or clarification was required. The discussion also addressed bioanalytical validation requirements of regulatory agencies, with the purpose of clarifying expectations for regulatory submissions. The proceedings from each day were reviewed and summarized in the evening sessions among the speakers and moderators of the day. The consensus summary was presented back to the workshop on the last day and was further debated. This communication represents the distillate of the workshop proceedings and provides the summary of consensus reached and also contains the validation topics where no consensus was reached.